Determinants of Firm Value and Its Implications on Stock Return of Banking Companies in Indonesia - Slamet Wahyudi (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This study aims to examine the effect of good corporate governance, macroeconomics, profitability and firm size on firm value which has implications for stock returns. Quantitative methods with panel data regression. The sample is 15 banking companies for the 2015-2021 period. The results show that 1) good corporate governance has no direct effect on stock returns but has a significant negative effect indirectly through firm value, 2) macroeconomics directly has a significant positive effect on stock returns but indirectly through firm value has no significant effect, 3 ) profitability either directly or indirectly through firm value has no significant effect on stock returns, 4) firm size either directly or indirectly through firm value has a significant positive effect on stock returns, 5) together good corporate governance, macro economy, profitability, and firm size have a significant positive effect on firm value, 6) together good corporate governance, macroeconomics, profitability, firm size and firm value have a significant positive effect on stock returns.